Preliminary Insights Into Project-Based Learning (PBL) Implementation to Enhance Learning at Elementary Schools in Pakistan - Junaid, Angela Ahmed (English Education Study Program Faculty of Teacher Training and Education, 2024)
Project-based learning (PBL) is an educational approach centered on students, with a focus on cultivating critical thinking, problem-solving skills, and collaborative abilities. Extensive evidence exists showcasing its effectiveness in nurturing 21st-century skills such as communication, creativity, and critical thinking. However, the successful integration of PBL into elementary school lessons faces challenges, with a number of determinants affecting its outcomes. This study aims to investigate teachers’practices in implementing PBL at elementary schools and the impact on student learning engagement and performance. Employing a qualitative approach, the study incorporates interviews with purposive samples who are experienced elementary school educators and this was complemented by classroom observations in PBL settings. The findings reveal that the teachers reported observable learning engagement improvements among their chargers and expressed a sense of gratification from their PBL lessons as they experience new and positive pedagogic challenges during the whole process. Findings from this research could serve as a useful guideline for elementary level PBL implementation. Furthermore, the results of this study provide deeper comprehension of the factors influencing teachers’ buy-in of PBL use in the and their implications for the nationwide adoption.